2008
DOI: 10.14356/kona.2008007
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Science and Technology of Diesel Particulate Filters

Abstract: As diesel emission regulations become more stringent, diesel particulate filters (DPFs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…TEM studies by Gardini et al [15] on Ag/soot mixtures have indicated that tight contact corresponds to an extensive interface between primary particles of catalyst and soot, whereas loose contact corresponds to fewer contact points at the interface between coagulates of catalyst particles and coagulates of soot particles. In several experiments [11,[16][17][18][19][20] with oxidation of soot particles filtered from gas streams by a catalytic filter part of the soot oxidation has been observed to peak at a relatively low temperature in the range characteristic of tight contact with the catalyst, while another part of the soot oxidation has been observed to peak at a higher temperature more characteristic of loose contact with the catalyst. Hence an understanding of both tight and loose contact oxidation may be relevant for real filter applications.…”
Section: Introductionmentioning
confidence: 99%
“…TEM studies by Gardini et al [15] on Ag/soot mixtures have indicated that tight contact corresponds to an extensive interface between primary particles of catalyst and soot, whereas loose contact corresponds to fewer contact points at the interface between coagulates of catalyst particles and coagulates of soot particles. In several experiments [11,[16][17][18][19][20] with oxidation of soot particles filtered from gas streams by a catalytic filter part of the soot oxidation has been observed to peak at a relatively low temperature in the range characteristic of tight contact with the catalyst, while another part of the soot oxidation has been observed to peak at a higher temperature more characteristic of loose contact with the catalyst. Hence an understanding of both tight and loose contact oxidation may be relevant for real filter applications.…”
Section: Introductionmentioning
confidence: 99%
“…In tests where soot and catalyst are crushed together (so-called tight contact), the oxidation occurs at a significantly lower temperature, compared to when soot and catalyst are stirred together with a spatula (so-called loose contact) [11]. Several experiments with diesel soot filters [10,[12][13][14][15] have indicated the presence of both contact types. An explanation of this may come from the environmental scanning electron microscopy experiments by Kameya and Lee [16], who observed that the catalytic oxidation at the interface between the bottom of the soot cake and the catalyst containing filter caused the soot cake to crack, leading to a delamination and subsequent diminishment or even loss of soot/catalyst contact [16].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, with increasingly stringent emission standards, the need for improved emission control systems for PM has become evident. Catalyst coated diesel particulate filter (DPF) is an efficient device to trap and simultaneously burn the soot within the exhaust temperature range (150-450 o C) [9]. The soot formula can be approximately given as C 8 H [10] which on combustion releases non-toxic gases found in the atmosphere.…”
Section: Canadian Chemical Transactionsmentioning
confidence: 99%